2022
DOI: 10.1186/s12933-022-01636-z
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional association of C-peptide with cardiovascular risk in nondiabetic adults and patients with newly diagnosed type 2 diabetes mellitus: a retrospective cohort study

Abstract: Background Recent literature reported the biological role of C-peptide, but this role is still controversial and unclear. The primary aim of this study was to investigate associations between C-peptide and cardiovascular biomarkers as well as events. Methods A total of 55636 participants who had a health examination from 2017 to 2021 were included. Of them, 6727 participants visited the hospital at least twice. Cardiovascular biomarkers like high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Further, Harnishsingh and colleagues found a relationship between C‐peptide levels, disease severity, and the existence of CAD 24 . Other studies have found significant relationships between C‐peptides, cardiovascular events, and mortality 25,26 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, Harnishsingh and colleagues found a relationship between C‐peptide levels, disease severity, and the existence of CAD 24 . Other studies have found significant relationships between C‐peptides, cardiovascular events, and mortality 25,26 …”
Section: Discussionmentioning
confidence: 98%
“…24 Other studies have found | 5 of 9 significant relationships between C-peptides, cardiovascular events, and mortality. 25,26 Basal C-peptide levels have also been linked with carotid artery intima-media thickness in T2DM patients 27,28 and myocardial infarction (MI) in the general population. 29 As such, the current study contributes to the expanding body of knowledge supporting the use of C-peptide as a stand-in biomarker for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the association between fasting C-peptide levels and cardio-vascular complications and shown that increased C-peptide levels are related to cardiovascular disorders complicating T2DM. [25][26][27]…”
Section: Discussionmentioning
confidence: 99%
“…So, they suggested further studies to overcome these limitations. 27 To the best of our knowledge, few studies have discussed the correlation between C-peptide levels and peripheral vascular atherosclerosis complicating type 2 DM, and they have not discussed the correlation with the severity of this complication.…”
mentioning
confidence: 99%
See 1 more Smart Citation